Acquired maxillary double lip - Chaithra Kalkur; Krishna Burde; Anusha R L; Nilofer Halim; Atul Sattur (Wolters Kluwer Medknow Publications, 2019)
Double lip is a rare deformity of the face, which can occur as congenital and acquired anomaly. It most often appears as syndromic variety along with systemic manifestations. It is a rare occurrence with slight male predilection. This article is a report of a 20-year-old female presented with the acquired double upper lip for 1 year developed after orthodontic treatment.